Determinan Kesiapan Berwirausaha Mahasiswa: Sebagai Aktor dalam Meningkatkan Ekonomi Kerakyatan - Ita Nuryana; Wijang Sakitri; Bestari Dwi Handayani; Agung Haryono; Menik Kurnia Siwi (Jurnal Ecogen, 2021)
This study investigates the entrepreneurial readiness of students by looking at the factors of self-efficacy, business opportunities and product creativity. The objectives of this study are to 1) Analyze the effect of self-efficacy on student entrepreneurship readiness. 2) Analyzing business opportunities that affect student entrepreneurship readiness 3) Analyzing product creativity affects student entrepreneurship readiness. This type of research is a quantitative study with a population of 121 students from the Faculty of Economics who have taken Entrepreneurship courses. Methods of collecting data using a questionnaire with data analysis techniques using descriptive analysis and SEM SmartPLS versi 3.0.. The results showed that 1) self-efficacy had a positive and significant effect on students' Entrepreneurial Readiness. 2) business opportunities have a positive and significant effect on students' Entrepreneurial Readiness. 3) Product creativity has a positive and significant impact on students' Entrepreneurial ReadinessKeywords : Self efficacy, Business Opportunities, Product Creativity and Entrepreneurial Readiness